PHYTOPLANKTON PRODUCTIVITY IN PAHUJ RESERVOIR, UTTAR PRADESH - BANIK, SURAJIT K.; DAS, A. K.; WANGANEO, A. (Journal of the Inland Fisheries Society of India, 2021)
Pahuj, a small reservoir, located at Jhansi in Uttar Pradesh, India was investigated during May 2007 to April 2009 for its phytoplankton productivity. The gross primary production (mg C m-2 d-1) was higher (8633) in 2007-08 than in 2008-09 (8159), but the net primary production was slightly higher during 2008-09 (5824) than in 2007-08 (5620). Physico-chemical features of water in this reservoir revealed that the reservoir is highly productive. Water pH was 7.52, average total alkalinity was 134 mg l-1 and average specific conductivity was 324 ÂµS cm-1 along with high values of dissolved oxygen, total hardness, calcium and phosphate-P.Key words: Pahuj reservoir, primary productivity, physico-chemical parameters.